Pencegahan Penyebaran Covid-19 Dengan Hand Sanitizer Pedal Di Kelurahan Wonocolo, Surabaya - Desrina Yusi Irawati; Jemmy Immanuel; Lewi Ardy Santosa (Lembaga Penelitian dan Pengabdian kepada Masyarakat, 2021)
Abstract: Covid-19 is an acute respiratory tract infection that is easily contagious. Wonocolo Village is one of the villages in Surabaya that is prone to the spread of Covid-19 due to high population mobilization. In addition, in the Wonocolo area RT 11 RW 4 does not yet have public hand sanitizer facilities. Public awareness about personal hygiene is also starting to decrease. By observing these phenomena and problems, a hand sanitizer pedal procurement activity was carried out in the Wonocolo RT 11 RW 4 area. The hand sanitizer pedal is operated by stepping on the foot to minimize the possibility of the spread of Covid-19 due to alternating hand touches. The method used is to make and install a hand sanitizer pedal, and explain how to operate it. The changes felt by residents from the procurement of pedal hand sanitizers are that the Wonocolo RT 11 RW 4 area has public hand sanitizer facilities. This indirectly reminds and familiarizes residents to clean their hands before and after activities outside the home. The activity went well and was greeted enthusiastically by the residents. It is evident from the participation of residents in helping the process of making and installing hand sanitizer pedals.